2015
DOI: 10.1021/ie5037287
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Biobased p-Xylene Production

Abstract: A general framework implementing process design, simulation, heat integration and Life Cycle Assessment (LCA) is illustrated to develop a sustainable route, which is particularly exploited to evaluate the environmental impacts of the p-xylene production from both generation biomass feedstocks. Noticeably, the lignocellulose-based p-xylene is comparable with the petroleumbased p-xylene whilst the starch-based p-xylene appears less environmentally friendly. In the latter case the cultivation and processing of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…The term in Table 2 18 fructose dehydration to HMF, and humin-formation reactions. [45] Therefore, below we evaluate the possibility of improving HMF yield by adding HCl to CrCl3 in aqueous solution. Figure 6 shows that most of the humins form from either fructose (>50% from Lewis acid-catalyzed reactions) or glucose (25-40% from Lewis acid-catalyzed reactions).…”
Section: Reactionmentioning
confidence: 99%
“…The term in Table 2 18 fructose dehydration to HMF, and humin-formation reactions. [45] Therefore, below we evaluate the possibility of improving HMF yield by adding HCl to CrCl3 in aqueous solution. Figure 6 shows that most of the humins form from either fructose (>50% from Lewis acid-catalyzed reactions) or glucose (25-40% from Lewis acid-catalyzed reactions).…”
Section: Reactionmentioning
confidence: 99%
“…In their recent ′Life cycle assessment of bio‐based p ‐xylene production′, Lin et al . concluded that production of p ‐xylene starting from starch and proceeding via Diels–Alder cycloaddition of DMF and ethylene was actually still less ′environmentally friendly′ than that derived from petroleum, highlighting the need to further improvements in the efficiency and sustainability of the process.…”
Section: Cycloaddition Of Biomass‐derived Furans and Suitable Dienopmentioning
confidence: 99%
“…The production of hemicellulose solutions using dilute acid hydrolysis has been previously examined in our work. 32 The economic analysis is based on the capital cost reported in Ref. 46 and scaled to first quarter of 2013 and capacity using in our simulation.…”
Section: Economic Analysismentioning
confidence: 99%
“…45 The biomass processing utilizes dilute acid hydrolysis and the detailed descriptions and the input and output inventory can be found in Ref. 32. The other scenario starts with hemicellulose solutions from paper mill which are often burnt to produce heat.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
See 1 more Smart Citation